Experimental and computational analysis of a pharmaceutical-grade shape memory polymer applied to the development of gastroretentive drug delivery systems. (December 2021) - Inverardi, N.; Scalet, G.; Melocchi, A.; Uboldi, M.; Maroni, A.; Zema, L.; Gazzaniga, A.; Auricchio, F.; Briatico-Vangosa, F.; Baldi, F.; Pandini, S.
Abstract: The present paper aims at developing an integrated experimental/computational approach towards the design of shape memory devices fabricated by hot-processing with potential for use as gastroretentive drug delivery systems (DDSs) and for personalized therapy if 4D printing is involved. The approach was tested on a plasticized poly(vinyl alcohol) (PVA) of pharmaceutical grade, with a glass transition temperature close to that of the human body (i.e., 37 °C). A comprehensive experimental analysis was conducted in order to fully characterize the PVA thermo-mechanical response as well as to provide the necessary data to calibrate and validate the numerical predictions, based on a thermo-viscoelastic constitutive model, implemented within a finite element framework. Particularly, a thorough thermal, mechanical, and shape memory characterization under different testing conditions and on different sample geometries was first performed. Then, a prototype consisting of an S-shaped device was fabricated, deformed in a temporary compact configuration and tested. Simulation results were compared with the results obtained from shape memory experiments carried out on the prototype. The proposed approach provided useful results and recommendations for the design of PVA-based shape memory DDSs.